Experimental calibration of parallel-to-grain strain penetration length for internal epoxied bars. (1st June 2016) - Sarti, Francesco; Palermo, Alessandro; Pampanin, Stefano
Highlights: Experimental quasi-static monotonic and cyclic testing of mild steel bars embedded in timber. Experimental data analysis and calibration of the parallel-to-grain strain penetration length for internal epoxy. Application to section analysis of the developed simplified analytical model. Abstract: Tensile strain penetration effects have been first investigated in the study of reinforced concrete components as experimental studies highlighted that theoretical values for the equivalent plastic hinge length did not reflect the observed experimental results. This is due to the elongation of the bars beyond the theoretical interface of the structural element with another component (e.g. beam-to-column or column/wall-to-foundation connections). The concept of an equivalent strain penetration length was first introduced for flexural analysis of concrete elements and the definition of the element's plastic hinge length. Experimentally calibrated expressions for the equivalent strain penetration length have been developed in literature and extensively adopted in the design of traditional reinforced concrete connections. Internal partially unbonded bars have more recently been used is precast concrete dissipative post-tensioned rocking systems, developed during the PREcast Seismic Structural Systems (PRESSS) program, and more recently in timber rocking (Pres-Lam). As per bars embedded or post-grouted into concrete, internally glued bars in timber are affected by tensile strain penetration effects. An important parameter involved in the design of dissipative rocking section as well as more traditional epoxied rods connections is the additional slip and consequent loss of stiffness, strength and energy dissipation due to strain penetration. The paper shows the determination of an equivalent strain penetration length in internal epoxied bars through the experimental testing of several specimens accounting for different geometric parameters. The final part of the paper discussed the experimental results in terms of bar slip proposing simplified analytical formulas.